2021
DOI: 10.1007/s40596-020-01389-5
|View full text |Cite
|
Sign up to set email alerts
|

Women in Academic Psychiatry: Inequities, Barriers, and Promising Solutions

Abstract: For the first time in US history, first-year female medical school matriculants (50.7%) outnumbered men (49.3%) in 2017 [1]. Moreover, in 2019, women accounted for 50.5% of all medical students for the first time [1]. Yet, female faculty continue to be underrepresented at the highest rankings in academic medicine as a whole and in psychiatry [2, 3]. Women represent only 26% and 32% of full professors among all medical faculty and psychiatry faculty, respectively, with a majority identified as White [3]. Struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The interested reader is encouraged to review previously mentioned papers (e.g., Hardeman et al, 2016a, b). It is outside the scope of this paper to further detail each specific type of discrimination and antidiscrimination work within those specific areas; these could easily be (and are) their own papers (e.g., disability: Meeks & Herzer, 2016;Meeks & Jain, 2018;Meeks & Neal-Boylan, 2020;VanPuymbrouck, Friedman, & Feldner, 2020;sexual orientation: Hill et al, 2020a, b;Lu et al, 2020;Vargas et al, 2020;gender: Agrawal, Madsen, & Lall, 2019;Borlik et al, 2021;Richter et al, 2020). Specific DEI terms used in this paper are defined above to ensure a common understanding.…”
Section: Introductionmentioning
confidence: 99%
“…The interested reader is encouraged to review previously mentioned papers (e.g., Hardeman et al, 2016a, b). It is outside the scope of this paper to further detail each specific type of discrimination and antidiscrimination work within those specific areas; these could easily be (and are) their own papers (e.g., disability: Meeks & Herzer, 2016;Meeks & Jain, 2018;Meeks & Neal-Boylan, 2020;VanPuymbrouck, Friedman, & Feldner, 2020;sexual orientation: Hill et al, 2020a, b;Lu et al, 2020;Vargas et al, 2020;gender: Agrawal, Madsen, & Lall, 2019;Borlik et al, 2021;Richter et al, 2020). Specific DEI terms used in this paper are defined above to ensure a common understanding.…”
Section: Introductionmentioning
confidence: 99%
“…When we examine data in the United Kingdom and the United States, while women are starting a career in academic psychiatry, their progression to senior roles is no better. It has been reported that there has been no increase in numbers of women reaching Professor of Psychiatry in the United States since 1980, and between 2013 and 2018, there was a drop in the number of women Professors of Psychiatry (Borlik et al, 2021; Sheikh et al, 2018). In the United Kingdom, data reported found that while 35% of members of the academic faculty within the Royal College of Psychiatrists were female, they represented only 10% of Professors (Dutta et al, 2010).…”
mentioning
confidence: 99%
“…The numerous obstacles encountered by UIM and women faculty are well documented and include: (a) explicit and insidious racism; (b) microaggressions; (c) devaluation of scholarly contributions, merit, and skillset by colleagues and administrators; (d) the burden of representing all minoritized populations; and (e) the continuous and disproportionate requests to serve on committees, task forces, and workgroups to fulfill institutional mandates to diversify representation that are generally uncompensated, undervalued and unaccounted for, in terms of promotion consideration and career advancement (i.e., minority tax) (24, 25,[27][28][29]. These experiences of both blatant and perceived discrimination, vocational strain, role overload, and adverse life events have also been shown to impact the physical and mental health of UIM faculty (27,28).…”
Section: Culturally Responsive Mentoring Mattersmentioning
confidence: 99%